Gut Microbiota Differs in Composition and Functionality Between Children With Type 1 Diabetes and MODY2 and Healthy Control Subjects: A Case-Control Study - Leiva-Gea, Isabel; Sánchez-Alcoholado, Lidia; Martín-Tejedor, Beatriz; Castellano-Castillo, Daniel; Moreno-Indias, Isabel; Urda-Cardona, Antonio; Tinahones, Francisco J; Fernández-García, José Carlos; Queipo-Ortuño, María Isabel (Diabetes care, 2018)
Type 1 diabetes is associated with compositional differences in gut microbiota. To date, no microbiome studies have been performed in maturity-onset diabetes of the young 2 (MODY2), a monogenic cause of diabetes. Gut microbiota of type 1 diabetes, MODY2, and healthy control subjects was compared. This was a case-control study in 15 children with type 1 diabetes, 15 children with MODY2, and 13 healthy children. Metabolic control and potential factors modifying gut microbiota were controlled. Microbiome composition was determined by 16S rRNA pyrosequencing. Compared with healthy control subjects, type 1 diabetes was associated with a significantly lower microbiota diversity, a significantly higher relative abundance of , , , , and genera, and a lower relative abundance of , , , and . Children with MODY2 showed a significantly higher abundance and a lower and abundance. Proinflammatory cytokines and lipopolysaccharides were increased in type 1 diabetes, and gut permeability (determined by zonulin levels) was significantly increased in type 1 diabetes and MODY2. The PICRUSt analysis found an increment of genes related to lipid and amino acid metabolism, ABC transport, lipopolysaccharide biosynthesis, arachidonic acid metabolism, antigen processing and presentation, and chemokine signaling pathways in type 1 diabetes. Gut microbiota in type 1 diabetes differs at taxonomic and functional levels not only in comparison with healthy subjects but fundamentally with regard to a model of nonautoimmune diabetes. Future longitudinal studies should be aimed at evaluating if the modulation of gut microbiota in patients with a high risk of type 1 diabetes could modify the natural history of this autoimmune disease.